Using magnesium hydroxide for ocean alkalinity enhancement: elucidating the role of formation conditions on material properties and dissolution kinetics - Shaw, Cody; Ringham, Mallory C.; Carter, Brendan R.; Tyka, Michael D.; Eisaman, Matthew D. (Frontiers in Climate, 2025)
Mg(OH)2 holds potential as an alkalinity source for Ocean Alkalinity Enhancement (OAE). In this study, Mg(OH)2 was produced via precipitation from the alkalinity exchange of NaOH addition into brine. Mineralogy characterization (XRD, EDS, SEM) and dissolution kinetics (total alkalinity release rates) were used to investigate the adoption of seawater-precipitated Mg(OH)2 for OAE and compared to industrial sources. XRD revealed industrial sources contained a higher degree of crystallinity of 0.83–0.85 compared to 0.16–0.33 for seawater-precipitated paste. Mg(OH)2 at a higher degree of crystallinity (>80%) had significantly slower dissolution rates than Mg(OH)2 with a lower degree of crystallinity (<20%). A strong inverse relation between degree of crystallinity and dissolution rate was found for both seawater-precipitated and industrial sourced Mg(OH)2. Despite similar elemental composition to industrial sources, seawater-precipitated Mg(OH)2 exhibited lower crystallinity resulting in faster and more complete dissolution, suggesting a potential advantage over other alkalinity sources. Its seemingly tunable dissolution kinetics due to crystallinity provides an opportunity to optimize the material for OAE and carbon dioxide removal efficiency.